Epidemiology of Cucumber mosaic virus on ginger and turmeric, and its suppression using silver nanoparticles - Buhari, Muhammad (2021)
Plant viruses have hampered vegetable crops production worldwide, causing huge economic losses. Viral diseases have also been reported in ginger with two viruses, Ginger mosaic virus and Ginger chlorotic fleck virus. Virus-like symptoms, such as mosaic, stripping and stunted growth pattern, were observed on the ginger and turmeric crops in the States of Selangor, Pahang and Perak of Malaysia and there was no prior study to unfold the pathogen inciting these symptoms. In principle, for disease management to be successful and feasible, proper and accurate identification of causal organisms must first be achieved. Consequently, a total of 60 ginger leaf samples, 20 from each State and 45 turmeric leaf samples, 15 from each State were collected. Enzyme-linked immunosorbent assay (ELISA) was first employed to index the virus, then nucleic acid extracted using cetyl trimethyl ammonium bromide (CTAB), after which reverse transcription polymerase chain reaction (RT-PCR) was conducted using CMV coat protein (CP) gene-specific primers and primers for GCFV. The expected amplicon of ~500 bp, which encodes 120 amino acids of the coding sequence of CMV CP gene was obtained, which was cloned and sequenced. In ginger plants, 23 % of the total samples were positive for CMV across the three States from the ELISA and RT-PCR assays, with 30 % of the samples in Selangor and 20 % of the samples gotten from each of Pahang and Perak States being detected as CMV-positive. Only one turmeric sample from Selangor was positive for CMV. The ginger and turmeric CMV isolates found in Malaysia, have 100% nucleotide similarity amongst themselves and shared 96% sequence homology with CMV cucumber isolate from Thailand (AJ810264) and tomato CMV isolate from China (KX525736) respectively. The ginger CMV and turmeric CMV isolates obtained from this study, were phylogenetically grouped into CMV subgroup I B. Electron microscopic analysis has confirmed the CMV isolates, when the virus was purified, negatively stained using uranyl acetate and viewed under high resolution electron microscope. GCFV was however not detected from the two crops in this study by RT-PCR assay. Pathogenicity test was conducted on the ginger and turmeric host plants by mechanical inoculation of the CMV-positive samples; ginger (TM3 isolate) and turmeric (TMR isolate). The inoculated test plants (100 %) showed similar symptoms of mosaic, stunting and stripping as observed in the field and confirmed CMV positive by CP gene through RT-PCR assay. CMV was also detected in three-month-old plants grown from CMV-infected rhizomes with 90 and 100 % infections in ginger and turmeric plants respectively. Host range studies conducted through a sap transmission technique showed nine plant species from six plant families as potential hosts for CMV isolated from ginger. The efficacy of silver nanoparticles (AgNPs) against CMV in ginger and turmeric plants was investigated by real time PCR. The virus concentration was significantly reduced by AgNPs (p<0.01) in the two plants from one-month post inoculation (MPI) up to 5 MPI. Thus, AgNPs has provided an avenue for the control of CMV infection in ginger and turmeric plants. The virus causing the symptoms of mosaic, stripping and stunting observed on ginger and turmeric plants, was unravelled, and identified as CMV, and its pathogenicity and host range were also conducted and reported in this study. Finally, silver nanoparticles were shown to suppress the CMV multiplication in ginger and turmeric plants.